Empowering Youths for Social Changes: Educational Initiatives in Gandaki Rural Municipality, Ward No. 6 - Adhikari, Anish (International Research Journal of MMC, 2024)
The study aims to discern the role of education on youth empowerment to promote health and sanitation, gender equality and awareness to address social issues for social changes in Gandaki Rural Municipality ward number 6. The survey study identified various challenges related to education for youth empowerment. The descriptive research design was used. The focused group discussions using semi-structured questionnaires were administered to the seven youths of Chepang/Praja community aged 15-19 years old residing in the ward number 6. The sample was selected using purposive sampling technique. The education the youth of Chepang/Praja community empowered through education demonstrated the ability to promotes health and sanitation, gender equality and create awareness to address social issues within their society. Major challenges identified includes reluctance to change by the senior citizens, lack of priority to the training that didn't provide allowances, the voices of youth are unheard, remote geographical location, lack the access to transportation, lacks appropriate resources and migration. The study suggested that the education brings positive social changes through empowering the youth in the promotion of health and sanitation, gender equality and creation of awareness to address the social changes.